2019
DOI: 10.1103/physreve.100.010401
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of power laws in noncritical neuronal systems

Abstract: Experimental and computational studies provide compelling evidence that neuronal systems are characterized by power-law distributions of neuronal avalanche sizes. This fact is interpreted as an indication that these systems are operating near criticality, and, in turn, typical properties of critical dynamical processes, such as optimal information transmission and stability, are attributed to neuronal systems. The purpose of this Rapid Communication is to show that the presence of power-law distributions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Moreover, such a heterogeneous structure imparts a functional advantage in that the criticality is robust against varying external inputs. These results substantially extend the existing understanding based on homogeneous systems [4,[27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
supporting
confidence: 77%
“…Moreover, such a heterogeneous structure imparts a functional advantage in that the criticality is robust against varying external inputs. These results substantially extend the existing understanding based on homogeneous systems [4,[27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
supporting
confidence: 77%
“…On the one hand, many subsequent works showed that the presence of power-law avalanches is not a sufficient condition for criticality, as they might emerge from different mechanisms 16 20 . A perhaps stronger test for criticality is whether the avalanche exponents satisfy the crackling-noise relation, a relation that connects the avalanche exponents to the scaling of the average avalanche size with its duration T 21 – 23 , defined by the exponent .…”
Section: Introductionmentioning
confidence: 99%
“…Our main focus is on models that exhibit scale-free dynamics as measured by avalanche size distributions. Such models are usually referred to as critical, although the presence of power laws in avalanches properties is not a sufficient condition for the dynamics to be critical [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%